2016
DOI: 10.1038/srep23921
|View full text |Cite
|
Sign up to set email alerts
|

Pentameric quaternary structure of the intracellular domain of serotonin type 3A receptors

Abstract: In spite of extensive efforts over decades an experimentally-derived structure of full-length eukaryotic pentameric ligand-gated ion channels (pLGICs) is still lacking. These pharmaceutically highly-relevant channels contain structurally well-conserved and characterized extracellular and transmembrane domains. The intracellular domain (ICD), however, has been orphaned in structural studies based on the consensus assumption of being largely disordered. In the present study, we demonstrate for the first time tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 38 publications
(45 reference statements)
4
39
0
Order By: Relevance
“…The crystal structure of the 5-HT 3A contains a partially resolved ICD with three distinct segments: the MX-helix following a Figure 3A). The direct interaction of the full-length ICD and RIC-3 had been shown previously in a similar experiment and the ICD construct here was used as a control [25]. MBP alone or omitting the RIC-3 in the pull-down did not reveal the presence of the prey protein.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…The crystal structure of the 5-HT 3A contains a partially resolved ICD with three distinct segments: the MX-helix following a Figure 3A). The direct interaction of the full-length ICD and RIC-3 had been shown previously in a similar experiment and the ICD construct here was used as a control [25]. MBP alone or omitting the RIC-3 in the pull-down did not reveal the presence of the prey protein.…”
Section: Resultssupporting
confidence: 68%
“…Resistance to inhibitors of cholinesterase (RIC-3) is a chaperon protein known to modulate maturation and membrane trafficking of some members of pLGICs. Previously we have shown that the ICD mediates this interaction [21][22][23] ,and that the ICD alone, in the absence of both ECD and TMD, interacts with RIC-3 [25].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations